'The anatomy of our discontent': from braining the mind to mindfulness for teachers. Issue 2 (4th March 2018) - Baker, Bernadette M.; Saari, Antti
ABSTRACT: This paper offers an overview of contemporary inscriptions of mindfulness, their conditions of possibility, and examples of the braining of mind on which contemporary neuro-meets-contemplative turns are dependent. We examine key nineteenth-century events integral to the formation of Biologies Old, in which historic debates over 'the death of God' in Western worldviews forge a space of finitude dedicated to fleshy materiality and the relocation of bios . We also examine what emerges in the wake of such debates, including how Biologies New and a transcendence/immanence horizon continues to reverberate through popular, contemporary recommendations for mindfulness in teaching.